(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
In this research was studied the effect of different concentrations of lavender oil on the growth of Alternaria citri and Drechslera dematioidea . All concentration revealed obvious inhibitor activity against both fungi the inhibitory effect differenced as difference of concentrate. The concentrations 0.06 – 0.04 – 0.03 – 0.02- 0.006 – 0.004 g/ml showed 100%inhibition against Drechslera dematioidea and the inhibition rate was 60% at 0.002g/ml concentration on the eleventh day of incubation The constrictions0.06 – 0.04 – 0.03 – 0.02- 0.006 – 0.004 – 0.002 g/ml showed complete inhibition against the Alternaria citri and at constrictions 0.01g/ml the percentage of inhibition was 30.55%. The minimum bactericidal concentrations ( MBC) of lavender oil was 0.006g/ml agaist Drechslera dematioidea and it was 0.002g/ml against Alternaria citri .